EXPLORING TEACHING STRATEGIES IN ENGLISH SPEAKING SKILL FOR VOCATIONAL HIGH SCHOOL STUDENTS - Mulis; Sarah Mustopa (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
Speaking is a skill that deserves attention as much as literary skills in both first and second language. To most people, mastering the speaking skill is the single most important aspect of learning a second or foreign language in terms of the ability to carry out communication in the language. The qualitative design of this research was chosen. The subjects involved in this research were the teacher and office governance automation students of Vocational High School, Al-Khozini. Further, the data collection technique used observation, interview, and document analysis. Then, an iterative technique was utilized which one data collection technique was followed by another one. Yet, data reduction, data display, and conclusion drawing were constructed. To obtain data related to teaching strategies, the researcher observed the teaching and learning activities while taking notes it was followed by an interview and document analysis such as a lesson plan as clarification or verification. This research revealed several teaching strategies used by the teacher in teaching speaking skill such as demonstration, role-play, drilling, and questioning strategies. And, this research suggests that the teacher should apply various blended- teaching strategies in the teaching and learning activities.